Tradisi Pembacaan Hizib Nahdlatul Wathan Terhadap Pembentukan Karakter Peserta Didik di SMA Nahdlatul Wathan Jakarta - Hipzon Hipzon (Universitas Muhammadiyah Mataram, 2026)
This study aims to analyze the implementation of the Hizib Nahdlatul Wathan recitation tradition and the concept of character building toward the development of student character at SMA Nahdlatul Wathan Jakarta. SMA Nahdlatul Wathan integrates the Hizib Nahdlatul Wathan, authored by TGKH. Muhammad Zainuddin Abdul Madjid, alongside the concept of character building as a distinctive institutional strategy. This descriptive qualitative research utilized data collection techniques comprising observation, interviews, and documentation. The findings indicate that the tradition of reciting the Hizib Nahdlatul Wathan and character building is systematically implemented at SMA Nahdlatul Wathan Jakarta. Furthermore, the combination of the Hizib Nahdlatul Wathan recitation tradition and concepts character building has proven effective in constructing the dimensions of faith, piety toward Allah SWT and noble character, mutual cooperation (gotong royong), creativity, and independence (mandiri). In conclusion, the tradition of reciting the HizibNahdlatul Wathan aligns seamlessly with the Profil Pelajar Pancasila (Pancasila Student Profile) framework in shaping student character at SMA Nahdlatul Wathan Jakarta